2018
DOI: 10.3390/ijfs6040086
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exchange Rate Volatility on International Trade and Foreign Direct Investment (FDI) in Developing Countries along “One Belt and One Road”

Abstract: The “One Belt and One Road” (OBOR) project was started by the Chinese government with the aim of achieving sustainable economic development and increasing cooperation with other countries. This project has five major objectives, which include (i) increasing trade flow, (ii) encouraging policy coordination, (iii) improving connectivity, (iv) obtaining financial integration, and (v) fortifying closeness between people. This paper aims to analyze the effect of exchange rate volatility on international trade and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 51 publications
(53 reference statements)
4
45
0
3
Order By: Relevance
“…Additionally, research by [36] revealed that the exchange-rate series exhibits empirical regularities such as clustering volatility, non-stationarity, non-normality, and serial correlation, which justify the application of the GARCH methodology. Another recent study by [37] that used GARCH(1,1) found that exchange rate volatility affects both international trade and foreign direct investment (FDI) significantly but negatively in countries engaged in OBOR (One Belt One Road is a global development strategy adopted by the Chinese government involving infrastructure development and investments in 152 countries and international organizations in Asia, Europe, Africa, the Middle East, and the Americas). [38] showed that the GARCH(1,1) model was more effective than other complicated GARCH models when they took 330 ARCH-type specifications into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, research by [36] revealed that the exchange-rate series exhibits empirical regularities such as clustering volatility, non-stationarity, non-normality, and serial correlation, which justify the application of the GARCH methodology. Another recent study by [37] that used GARCH(1,1) found that exchange rate volatility affects both international trade and foreign direct investment (FDI) significantly but negatively in countries engaged in OBOR (One Belt One Road is a global development strategy adopted by the Chinese government involving infrastructure development and investments in 152 countries and international organizations in Asia, Europe, Africa, the Middle East, and the Americas). [38] showed that the GARCH(1,1) model was more effective than other complicated GARCH models when they took 330 ARCH-type specifications into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…Exchange rate stability is one important consideration for investors to take investment policies. If the exchange rate has high fluctuations, this can affect interest rates, commodity prices and a country's economic policy [1][2][3][4]. Then, if it is continued for a long time, it will affect investment policy.…”
Section: Introductionmentioning
confidence: 99%
“…He recommended the adherence to sound exchange rate management, which has the tendency of increasing production at the domestic level. Latief and Lefen (2018) and Campa and Goldberg (1993) studied the linkage between exchange rates, international trade and investment, emphasizing the role of producer exposure through export sales and inputs of production. Latief and Lefen used the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) (1,1) and Threshold-Generalized Autoregressive Conditional Heteroscedasticity (TGARCH) (1,1) whiles Campa and Godberg used two estimates of exchange rate volatility that is (i) the ratio of the standard deviation to the mean of the exchange rate index over the previous twelve quarters (ii) the standard deviation of the first differences of the logarithm of the exchange rate over the twelve previous quarters.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of the dollar on non-manufacturing industries was vague, its depreciations (appreciations), decreased (increased) investment in the non-durables manufacturing sector. Latief and Lefen (2018) have noted again that, exchange rate volatility has significant impact on both international trade and FDI and that, exchange rate volatility can potentially hurt international trade and FDI. Maepa (2016); Jeanneret (2010); Zolghadr (2009); Campa and Goldberg, (1999) found a negative relationship between exchange rate volatility and investment.…”
Section: Introductionmentioning
confidence: 99%